EVALUATION OF LABORATORY-IMMUNOLOGIC METHODS OF CARDIOVASCULAR PATHOLOGY IN PSORIATIC ARTHRITIS PATIENTS - Abdullaev U.S.; Abdullaev Ulugbek Sayfullaevich (Scholar Express Journals, 2023)
According to modern researchers, one of the most common comorbid diseases in patients with psoriatic arthritis (PsA) is cardiovascular disease (CVD). The presence of CVD in PsA increases the risk of cardiovascular complications (CVC) that lead to early disability in patients with this disease. In general, it was found that early diagnosis of CVD in PsA, not only can prevent CVC, but also can significantly improve the tactics of patient management, prevention of complications and improve the quality of life of patients with PsA
Keywords: psoriatic arthritis; cardiovascular diseases; laboratory-immunologic methods of research